Transcriptional profiling of Petunia seedlings reveals candidate regulators of the cold stress response - Li, Bei; Ning, Luyun; Zhang, Junwei; Bao, Manzhu; Zhang, Wei (Frontiers in Plant Science, 2015)
Petunias are important ornamentals with the capacity for cold acclimation. So far, there is limited information concerning gene regulation and signaling pathways related to the cold stress response in petunias. A custom-designed petunia microarray representing 24816 genes was used to perform transcriptome profiling in petunia seedlings subjected to cold at 2°C for 0.5 h, 2 h, 24 h and 5 d. A total of 2071 transcripts displayed differential expression patterns under cold stress, of which 1149 were up-regulated and 922 were down-regulated. Gene ontology enrichment analysis demarcated related biological processes, suggesting a possible link between flavonoid metabolism and plant adaptation to low temperatures. Many novel stress-responsive regulators were revealed, suggesting that diverse regulatory pathways may exist in petunias in addition to the well-characterized CBF pathway. The expression changes of selected genes under cold and other abiotic stress conditions were confirmed by real-time RT-PCR. Furthermore, weighted gene co-expression network analysis divided the petunia genes on the array into 65 modules that showed high co-expression and identified stress-specific hub genes with high connectivity. Our identification of these transcriptional responses and groups of differentially expressed regulators will facilitate the functional dissection of the molecular mechanism in petunias responding to environment stresses and extend our ability to improve cold tolerance in plants.